Anchor Coil Technique for Arteriovenous Fistula Embolization: A Technical Note. Issue 3 (May 2014) - Kanemaru, Kazuya; Ezura, Masayuki; Nishiyama, Yoshihisa; Yagi, Takashi; Yoshioka, Hideyuki; Fukumoto, Yuichiro; Horikoshi, Toru; Kinouchi, Hiroyuki
We describe a case of arteriovenous fistula (AVF) successfully treated by coil embolization with an anchor coil inserted in the varix to facilitate dense packing at the shunting site. AVF of the left anterior choroidal artery (AChoA) draining into the ipsilateral basal vein of Rosenthal was incidentally found in a newborn female. A single detachable coil was inserted as an anchor into the varix adjacent to the shunt, and the microcatheter was pulled back to the shunting point. Three more detachable coils were delivered at the shunting point without migration under the support of the anchor coil, and the AVF was successfully obliterated with preservation of AChoA blood flow. The anchor coil technique can reduce the risk of coil migration and the number of coils required.